Pengaruh Technology Oriented pada Customers terhadap Pertumbuhan Ekonomi Sektor Perdagangan Provinsi Jawa Timur - Putri Isnaeni, Widya Okta; Oktafia, Renny (Advances In Social Humanities Research, 2024)
The development of information and communication technologies has given rise to many changes, as if all the activities that take place in this world always involve technology in it. Appropriate use of technology, provides positive influences that create opportunities and innovations that can be exploited for the advancement of various sectors, especially the economy of the trade sector. One of the forms of implementation created due to the development of technology and information in the world is online commerce is the level of awareness of the public to prefer products of technological processing with good quality. This behavior is called Technology Oriented in Customers. The use of technology in the world of trade, where trade is one of the activities that affects economic growth, should be increased in order to support the magnitude of the economic growth of the trade sector. Therefore, this study was conducted with the aim of analyzing the results of Technology Oriented Practice on Customers which has more or less begun to be adopted by the East Java community as a form of technology implementation in the trade sector, mainly the sales level can affect the amount of numbers that can increase the value gain of the trade sector for East Java Province. By processing secondary data using multiple linear regression analysis methods. This study found that the influence of the Internet for sales did not have a significant effect on the trade sector because the number of sales made through the Internet is still lacking. The people of East Java tend to play the role of consumers. This reality is unfortunate because with good use of the digital economy, it can support the number of increased economic growth of the trade sector in East Java.